The globalization of foreign investment in Africa : the role of Europe, China and India - Bodomo, Adams (Emerald Publishing Limited, 2017)
The 21st Century era of globalization has opened up many investment alternatives for Africa. This book examines the role of foreign direct investment (FDI) in Africa's socio-economic development with particular reference to Europe and Asia's two biggest emerging economic powers, China and India. The book starts with a focus on the conceptualizations of FDI and the debate about its benefits or otherwise to the economic development and political sovereignty of the recipient country. It then provides a historical overview of FDI in Africa, arguing that a paradigm shift occurred with China's 21st Century intensified foray into Africa in search of oil and other raw materials to fuel its rapidly rising economy. The book then explores India's presence in Africa, and how it had to wake up to challenge the sudden rise in Chinese investment in the country with its "Focus - Africa" investment programme. This is followed by a brief overview of new emerging players in the African Investment stratosphere, with particular reference to other 'BRIC' countries such as Brazil and Russia. The book concludes with the idea that maintaining clear investment alternatives in Africa's investment stratosphere presents the best scenario for an African economic renaissance in the 21st Century. As Africa becomes a locus for an intensified investment by both traditionally powerful economies and emerging powers, this book provides both a much needed overview and new proposals for foreign investment in the nation.